(untitled) (Research, Society and Development, 2022)
The Unified Health System - SUS in Brazil is considered one of the most inclusive health systems in the world, mainly through its Family Health Units (FHUs) that are decisive in the fight against COVID-19, a disease which generates from respiratory infections even the cases of Severe Acute Respiratory Syndrome (SARS). Its propagation by droplets eliminated via sneezes, coughs and speech explain its easy spread, which demands preventive and educational prophylactic actions. In the city of Belém, a plan was developed based on the importance of Family Health Units (FHUs). In this context, the present study aimed to analyze the possibility of a correlation between the localization of FHUs in the municipality of Belém with the percentage infected with SARS-CoV-2 of their assigned population. For this, a quantitative ecological study of comparative analysis was used, carried out with data related to reported cases of infection by Sars-Cov-2 in the city of Belém in the period from 04/01/2020 to 03/31/2021. It was observed through the Pearson correlation (r) and descriptive statistics, lower average infection rates in neighborhoods where there are FHUs compared to neighborhoods where this service is not present. Through the results of the tests, it is concluded that, despite showing a weak correlation, since the number of existing units in the neighborhood did not influence the result, the relationship between the presence of FHUs and a lower rate of infection by SARS- CoV-2.